Coastal community resilience to flooding and tidal inundation in Semarang city in the context of the COVID-19 Pandemic - Putri, Shinta (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2026)
This study is motivated by the high vulnerability faced by communities affected by floods and tidal inundation in sustaining their livelihoods during the COVID-19 pandemic. Although numerous studies have examined the impacts of floods or the pandemic separately, research systematically assessing community resilience to multi-hazard events in coastal areas remains very limited. This study aims to evaluate the resilience level of communities affected by floods and tidal inundation in Semarang City in the context of the COVID-19 pandemic. This is a quantitative study, with data collected through questionnaires from 200 respondents who are communities affected by floods and tidal inundation. The sampling technique employed was stratified random sampling based on the drainage system coverage areas in Semarang City. Data were analyzed using scoring analysis and descriptive statistics. The results indicate that the resilience of communities affected by floods and tidal inundation during the COVID-19 pandemic in Semarang City is still moderate, particularly in terms of social, economic, and residential infrastructure resilience. The study implies an increase in vulnerability among Semarang City communities to floods and tidal inundation during the pandemic. Theoretically, this research contributes to the study of multi-hazard community resilience by identifying indicators that determine the adaptive capacity of coastal communities facing hydrometeorological risks concurrently with a health crisis. Practically, the findings can serve as a reference for the Semarang City Government to enhance community resilience based on the suboptimal indicators identified through this study.   Penelitian ini dilatarbelakangi oleh tingginya kerentanan yang dihadapi masyarakat terdampak banjir dan rob dalam bertahan selama pandemi COVID-19. Meskipun banyak penelitian telah menelaah dampak banjir atau pandemi secara terpisah, studi yang secara sistematis menilai ketahanan masyarakat terhadap bencana multi-bahaya di wilayah pesisir masih sangat terbatas. Penelitian ini bertujuan untuk menilai tingkat ketahanan masyarakat terdampak banjir dan rob di Kota Semarang dalam menghadapi pandemi COVID-19. Penelitian ini merupakan penelitian kuantitatif. Data dikumpulkan melalui kuesioner dengan sejumlah 200 responden yang merupakan masyarakat terdampak banjir dan rob. Teknik sampling yang digunakan dalam penelitian ini adalah stratified random sampling didasarkan pada masing-masing wilayah cakupan sistem drainase di Kota Semarang. Data kemudian dianalisis menggunakan teknik analisis skoring dan statistik deskriptif. Hasil penelitian menunjukkan bahwa ketahanan masyarakat terdampak banjir dan rob di Kota Semarang dalam menghadapi pandemi covid-19 masih tergolong sedang. Hasil ini utamanya terlihat pada ketahanan sosial, ekonomi, dan infrastruktur lingkungan tempat tinggal penduduk. Penelitian ini berimplikasi pada kerentanan masyarakat Kota Semarang dalam menghadapi banjir dan rob yang ternyata meningkat dalam menghadapi pandemi covid-19. Secara teoretis, penelitian ini berkontribusi pada studi ketahanan komunitas multi-bahaya dengan mengidentifikasi indikator-indikator yang menentukan kapasitas adaptif masyarakat pesisir terhadap risiko hidrometeorologis yang bersamaan dengan krisis kesehatan. Secara praktis, penelitian ini dapat menjadi acuan bagi Pemerintah Kota Semarang untuk meningkatkan ketahanan masyarakat berdasarkan indikator-indikator yang kurang optimal yang berhasil diidentifikasi melalui penelitian ini.